2021
DOI: 10.1017/s1537592721000013
|View full text |Cite
|
Sign up to set email alerts
|

No Right to Be Wrong: What Americans Think about Civil-Military Relations

Abstract: An influential model of democratic civil-military relations insists that civilian politicians and officials, accountable to the public, have “the right to be wrong” about the use of force: they, not senior military officers, decide when force will be used and set military strategy. While polls have routinely asked about Americans’ trust in the military, they have rarely probed deeply into Americans’ views of civil-military relations. We report and analyze the results of a June 2019 survey that yields two impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Given that the public expresses a surprising degree of comfort with and deference to policy advocacy by senior military officials even on non-military issues, however, presidents may still reasonably worry about military opposition in such contexts. 143 Indeed, the history of high-profile civil-military friction over contentious policies in peacetime -notably including the debate over "don't ask, don't tell" -offers prima facie evidence that presidents may face incentives to employ one or more of the strategies identified in this article across any issue that is sufficiently salient to attract public attention.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Given that the public expresses a surprising degree of comfort with and deference to policy advocacy by senior military officials even on non-military issues, however, presidents may still reasonably worry about military opposition in such contexts. 143 Indeed, the history of high-profile civil-military friction over contentious policies in peacetime -notably including the debate over "don't ask, don't tell" -offers prima facie evidence that presidents may face incentives to employ one or more of the strategies identified in this article across any issue that is sufficiently salient to attract public attention.…”
Section: Discussionmentioning
confidence: 95%
“…25 A 2019 survey, meanwhile, found that over 45% of respondents felt that the president should use U.S. forces on the battlefield as the senior military leadership advised, even if the president disagreed with them. 26 This dynamic serves to discourage civilian leaders from questioning or countermanding the preferences of the "armed servants" they oversee. As James Cartwright, who served as Vice Chairman of the JCS during the period studied in this article, puts it, "the country spends all this time saying how wonderful the military is, so politically it's very difficult to criticize them."…”
Section: The Political Cost Of Civilian Controlmentioning
confidence: 99%
“…Recent research suggests a decline in the number of compromise options available to political elites has important implications for civil-military relations. In a survey with questions about deference to the military and presidential response to proposals from the military, citizen responses fell along partisan lines (Krebs et al, 2021). This suggests Americans understand civil-military relations through a partisan lens.…”
Section: Example 1: Separation Of Powers and Political Polarizationmentioning
confidence: 99%
“…Krebs et al (2018) find that nearly 70% of Americans now believe that the country should defer, at least in part, to the military's judgments on whether to use military force. Krebs et al (2021), similarly, find that about half the US public believes the president should follow the military's recommendation on the use of force even when the president disagrees. These studies raise a compelling, and as of yet unanswered, question about whether contemporary public deference to military judgments coincide with an underlying narrowing of the Huntingtonian public-military gap in foreign policy beliefs, or if American citizens trust the military despite differences in those core beliefs?…”
Section: Introductionmentioning
confidence: 97%